2022
DOI: 10.1155/2022/3062526
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Cardiovascular Risk Factors, Clinical Presentation, and Outcome of Patients Admitted with a Hypertensive Crisis at the Buea Regional Hospital, Cameroon

Abstract: Background. Several recent studies have shown differences in the risk profile and outcome of cardiovascular diseases between men and women, with a dearth of data from African populations. This study aimed to examine gender differences in a group of patients from Cameroon hospitalized with a hypertensive crisis. Methods. We conducted a cross-sectional study from June 2018 until June 2019. The criteria to define a hypertensive crisis (HC) were systolic and/or diastolic blood pressure should be ≥180/110 mmHg. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…For the incidence of stroke onset by subtype among background characteristics, cerebral hemorrhage was slightly more common and cerebral infarction was less common in this study. For stroke incidence by sex in this study, stroke was more commonly observed in men, although this result was similar to those observed in the studies involving patients with mild stroke as in this study 16,17. In addition, for the medical history (risk factors) at the onset of stroke, many participants had hypertension in this study, which was a similar result to that obtained in the study on risk factors in Japanese patients with stroke 18.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For the incidence of stroke onset by subtype among background characteristics, cerebral hemorrhage was slightly more common and cerebral infarction was less common in this study. For stroke incidence by sex in this study, stroke was more commonly observed in men, although this result was similar to those observed in the studies involving patients with mild stroke as in this study 16,17. In addition, for the medical history (risk factors) at the onset of stroke, many participants had hypertension in this study, which was a similar result to that obtained in the study on risk factors in Japanese patients with stroke 18.…”
Section: Discussionsupporting
confidence: 89%
“…For stroke incidence by sex in this study, stroke was more commonly observed in men, although this result was similar to those observed in the studies involving patients with mild stroke as in this study. 16,17 In addition, for the medical history (risk factors) at the onset of stroke, many participants had hypertension in this study, which was a similar result to that obtained in the study on risk factors in Japanese patients with stroke. 18 As for behaviors before stroke onset, approximately 80% of participants did not perform home blood pressure measurements, demonstrating evidence of a failure of self-monitoring with home blood pressure measurement.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were observed in another study using National Inpatient Database (NIS), which might be explained by the higher comorbid conditions in men than women [ 9 ]. In that study, it was also observed that men admitted with hypertensive crises were younger than women, which might be due to the fact that blood pressure control worsens in women as they grow older [ 9 ], which is linked to hormone changes [ 10 , 11 ]. On the contrary, one study found that female patients were 2.494 times more likely to develop hypertensive emergencies than males (95% CI: 1.111‒5.596).…”
Section: Discussionmentioning
confidence: 99%
“…There has also been a recently recognized sex disparity, with the rates of hospitalization for HTN-E rising faster in men than women in the United States [9]. Other countries have not found this to be the case, with an equal number of men and women being admitted with HTN-C [10].…”
Section: Epidemiologymentioning
confidence: 99%